Investigating Energy Consumption of an SRAM-based FPGA for Duty-Cycle Applications - Shahzad, Khurram; Oelmann, Bengt (Parallel computing : accelerating computational science and engineering (CSE), 2014)
In order to conserve energy, battery powered embedded systems are typically designed with very low-power modules that offer limited computational power and communication bandwidth and therefore, are generally applicable to low-sample-rate intermittent applications. On the other hand, enabling an embedded system with a high-throughput processing resource such as an FPGA, high-throughput processing performance that is typically required in high-sample rate monitoring applications can be achieved. However, the high power consumption associated with an FPGA poses a major challenge in attaining significant lifetime for a battery-powered embedded system. In this paper, we investigate energy consumption of an SRAM-based FPGA in relation to duty-cycle applications. In order to achieve long operational lifetime in an FPGA-based embedded system, the possible options to dynamically manage the power consumption are studied and discussed. The experimental results suggest that the SRAM-based FPGA, XC6SLX16 that provides ample logic resources in relation to typical high-sample rate monitoring applications, can be used in a battery operated embedded systems while minimizing the energy consumption to 2.56 mJ for inactive duration of 235 ms or above.